Antibacterial Potential of Star Anise (Illicium verum Hook. f.) Against Food Pathogen Bacteria - EVELINE EVELINE; AGUSTIN NOVITA (Indonesian Society for microbiology, 2020)
Star anise (Illicium verum Hook. f.) is commonly used as spice and flavor enhancer in food. Previous research revealed the presence of active compound which could inhibit bacterial growth. Thus, in order to apply star anise as natural antibacterial agent in food product, a further research concerning antibacterial activity and stability of star anise was conducted. Crude extract of star anise was obtained using ethanol and acetone with maceration method for 3 days, then diluted to 10, 20, 30, 40, and 50% (w/v). Well diffusion was conducted against three food spoilage bacteria (Staphylococcus aureus, Escherichia coli, and Bacillus cereus). Extract from ethanol with 30% concentration was selected as the best extract in which inhibit more than 6 mm inhibition zone with MIC and MBC value: 1.59% and 6.36% (S. aureus), 1.04% and 4.18% (E. coli), and 0.59% and 2.39% (B. cereus). This selected extract was used to test the extract stability against 4 levels of heating temperature (60, 70, 80, and 90Â°C) for 2 levels of heating time (15 and 30 minutes), and 4 levels of pH (4, 5, 6, and 7). Based on our results, different heating treatment and pH caused extract instability. Star anise extract was more stable at 60Â°C for 15 minutes heating treatment and pH 4, which resulting the lowest inhibition zone reduction compared to control extract. Star anise extract was categorized as low toxic compound (LC50 = 212.09 ppm). Terpenoids (anethole, 2,6-dimethyl-6-(4-methyl-3-pentenyl)-2-norpinene, Î²-caryophyllene, Î²-bisabolene) was founded as major antibacterial compound in star anise extract; fatty acid (6-octadecenoic acid, hexadecanoic acid, stearic acid) and benzaldehyde (4-anisaldehyde, p-allylanisole) were also founded as minor compound.